Causal association between inflammatory bowel disease and IgA nephropathy: A bidirectional two-sample Mendelian randomization study - Xiao, Mofan; Ran, Yan; Shao, Jiayuan; Lei, Zhangni; Chen, Yuling; Li, Yingchao (Frontiers in Genetics, 2022)
Background: An association between inflammatory bowel disease (IBD) [including ulcerative colitis (UC) and Crohn’s disease (CD)] and IgA nephropathy (IgAN) has been discovered in observational studies, but the causal relationship was still unknown. The aim of this study was to clarify the causal link between IBD (including UC and CD) and IgAN via two-sample Mendelian randomization (MR) analysis. Methods: Eligible single nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs) for analysis and were obtained from publicly available genome-wide association study (GWAS) summary statistics. Inverse-variance weighting (IVW), Mendelian randomization Egger (MR‒Egger) regression, the Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) test and the weighted median were utilized to obtain the results. The MR-PRESSO test and MR‒Egger regression were also performed to detect and correct horizontal pleiotropy. Cochran’s Q test and “leave-one-out” analysis were also conducted to assess the stability and reliability of the MR results. Results: This study found that IBD, UC and CD all had a significant positive causal effect on IgAN risk (IBD: OR=1.58, 95% CI 1.15-2.16, P=4.53×10-3; UC: OR=1.55, 95% CI 1.14-2.11, P=4.88×10-3; CD: OR=1.57, 95% CI 1.21-2.03, P=5.97×10-4). No significant horizontal pleiotropic effect was found for the causal association between IBD, UC, CD and the risk of IgAN. Cochran’s Q test identified no evidence of heterogeneity for the IV estimates. The “leave-one-out” sensitivity analysis also revealed that the MR results were robust. Conclusion: The results of this two-sample MR analysis supported that IBD, UC and CD were causally associated with the risk of IgAN, while there was no sufficient evidence for the causal effect of IgAN on IBD, UC or CD. Our findings provided theoretical support and a new perspective for the diagnosis and treatment of these two diseases.